A motivação sobre a valoração da prova testemunhal pela perspectiva de adequação ao dever de fundamentação das decisões judiciais no modelo constitucional de processo penal - Arnaldo Lares Campagnani (2019)
This work seeks to study the reasoning of judicial sentences from a perspective that meets the democratic parameters imposed by the Constitution to the criminal procedure. The inquisitorial genesis of Brazilian criminal procedure was first distinguished and then it was assumed that criminal trials are a juridical form of enunciating the truth that relates knowledge and ruling. Established these grounds it was addressed the problem of how sentencing can be performed in a democratic way, thus moving the attention to the relationship between democratic rule by law and criminal procedure. The duty to state reasons for judicial decisions on criminal adjudication is then stablished in a very specifically relation with the definition of criminal procedure framed a adversarial parties system, which has its repercussion in the very object of the research. More than the indication of the reasons by the judge, it was tried to demonstrate how reasoning should be the corollary of a democratic process that shall enable the merge of views presented by the parties during the trial, providing the means for a sentence that lies on the effective participation of those possibly affected by it. In order to test the hypothesis that currently the reasoning of the decisions regarding the facts does not meet these democratic parameters, it was made the analysis of evaluation basis of the testimonial evidence in the scope of the Tribunal de Justiça de Minas Gerais. The analyzed judgments compose the empirical control sample regarding the results of the research.